Variant anatomy of common hepatic artery and its branching pattern: a cadaveric study with clinical implication - Thamke, Swati; Rani, Pooja (International Journal of Research in Medical Sciences, 2017)
Background: With the advent of new diagnostic, therapeutic and operative techniques within the abdominal cavity, a sound knowledge of the variant courses of the abdominal vessels become important for dealing clinicians, surgeons and interventional radiologists. Surgeons undertaking hepatobiliary and gastric surgery must be acquainted with the anatomy of common hepatic artery and should be able to recognize its multiple anatomical variants to avoid subsequent thrombosis leading to ischaemia of the liver or bile duct and stomach with distressing consequences. The present study was carried out to document the normal anatomy and different variations of the common hepatic artery and to evaluate the possible clinical implications. Methods: A total of 36 properly embalmed and formalin fixed cadavers were dissected in the abdominal region and viscera were mobilized to expose the origin of important branches of the common hepatic artery. Results: Classical branching pattern of common hepatic artery was seen in 91.66% cases. Origin of right hepatic artery from superior mesenteric artery and accessory cystic artery from gastroduodenal artery was seen in 2.77% cases. In 5.55% cases, right gastric artery originated from left hepatic artery. Conclusions: Knowledge of such variations will play a significant role in avoiding technical difficulties during infusion therapy and chemoembolization of neoplasm in the liver. It is also valuable in carrying out surgical intervention safely in the abdomen and also in the interpretation of angiographic reports.